PELATIHAN ORIGAMI DAN POP-UP BAGI GURU TK DIAN PERTIWI UNTUK MEMPERKENALKAN HEWAN PELIHARAAN - Hidajat, Henny; Streit, Aprilia Kartini (Jurnal Pengabdian dan Kewirausahaan, 2022)
Early Child Education (ECE) students, who are 3-6 years old, are in Pre-Operation cognitive stage, that trying to recognize all their surroundings. ECE schools manage to introduce them simple objects, animals, their families and others. Furthermore, school also train students to be ready for reading, writing and counting. Art lesson can be one method to introduce objects and their environment, also to practice their fine motor skills. TK Dian Pertiwi as one of ECE school also implement art lesson in their curriculum. However, since the teachers are having more concern on other skills development and not all of teachers are having interest and skill on art either, it is necessary to execute a training to upgrade teacher’s ability on developing and delivering the art lesson to the students in attractive and educative method, that it may expand students’ cognitive ability as well. Therefore, in January 10, 2022 Visual Communication Design Department of Bunda Mulia University executed a training for TK Dian Pertiwi Teachers as community service activity.  The training titled“Creative Origami and Pop Up to Introduce Pet Animals for ECE Students”, was executed online using Gmeet platform, due to Large Scale Social Restriction Policy announced by Republic of Indonesia government caused by Covid-19 Pandemic. The training was divided into two sessions to explain about origami and pop up. Both sessions presented information such as history, benefit, types, basic technic, materials, and demonstration about how to make origami and pop-up forming pet animals, such as cat, dog, rabbit, and other pets. The participant followed both demonstration by doing the instruction and making their own origami and pop up. After the training participants are able to create pet animals using origami and pop-up technics, choosing appropriate materials, recognize the benefit of both technics and having inspiration to develop the art lessons.